2017
DOI: 10.3389/fpls.2017.01504
|View full text |Cite
|
Sign up to set email alerts
|

Prioritizing Crop Management to Increase Nitrogen Use Efficiency in Australian Sugarcane Crops

Abstract: Sugarcane production relies on the application of large amounts of nitrogen (N) fertilizer. However, application of N in excess of crop needs can lead to loss of N to the environment, which can negatively impact ecosystems. This is of particular concern in Australia where the majority of sugarcane is grown within catchments that drain directly into the World Heritage listed Great Barrier Reef Marine Park. Multiple factors that impact crop yield and N inputs of sugarcane production systems can affect N use effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(44 citation statements)
references
References 55 publications
0
44
0
Order By: Relevance
“…Fertilization is an essential agricultural practice in terms of improving nutrient storage of plants and causing simultaneous changes in soil properties and microbial communities [5,6]. Sugarcane planting systems that are based on extensive fertilization, especially nitrogen, have been adopted to increase sugarcane production to meet increasing sugar demand over the past few decades [7]. Although inorganic fertilizers have a positive impact on sugarcane yield [8], they may also have indirect adverse effects on the environment and soil quality, such as through soil acidification [9], an increase in soilborne pathogens [10], enhanced nitrification, and nitrate leaching [11].…”
Section: Introductionmentioning
confidence: 99%
“…Fertilization is an essential agricultural practice in terms of improving nutrient storage of plants and causing simultaneous changes in soil properties and microbial communities [5,6]. Sugarcane planting systems that are based on extensive fertilization, especially nitrogen, have been adopted to increase sugarcane production to meet increasing sugar demand over the past few decades [7]. Although inorganic fertilizers have a positive impact on sugarcane yield [8], they may also have indirect adverse effects on the environment and soil quality, such as through soil acidification [9], an increase in soilborne pathogens [10], enhanced nitrification, and nitrate leaching [11].…”
Section: Introductionmentioning
confidence: 99%
“…This fact causes sub or super estimates of the N doses to be applied to the crop. In this scenario, new works [7,16] seek the development of strategies for the management of nitrogen fertilization in sugarcane plantations, aiming to increase nitrogen fertilization efficiency.…”
Section: Nitrogen Fertilization: Definition Of the Correct Source Apmentioning
confidence: 99%
“…Minimising and managing N inputs to optimise sugarcane yield is a priority for the Australian sugarcane industry. Approaches include the selection of sugarcane cultivars with superior N use efficiency (Robinson et al, 2011) and agronomic strategies that improve N fertiliser use (Thorburn et al, 2017, Bell et al, 2014. A simulation study identified N fertiliser rates more prominently affecting N use efficiency (NUE) (Thorburn et al, 2017) than management practices such as timing of fertiliser application, splitting N application, tillage intensity and in-field traffic management.…”
Section: Relationship Between N2o Emissions and Agronomic Efficiency mentioning
confidence: 99%
“…Approaches include the selection of sugarcane cultivars with superior N use efficiency (Robinson et al, 2011) and agronomic strategies that improve N fertiliser use (Thorburn et al, 2017, Bell et al, 2014. A simulation study identified N fertiliser rates more prominently affecting N use efficiency (NUE) (Thorburn et al, 2017) than management practices such as timing of fertiliser application, splitting N application, tillage intensity and in-field traffic management. Agronomic efficiency of fertiliser is an indication of how much additional cane (above the amount produced with zero N fertiliser) is produced per kg of N applied, and these values increased in reduced N treatments.…”
Section: Relationship Between N2o Emissions and Agronomic Efficiency mentioning
confidence: 99%
See 1 more Smart Citation